Generation of Gene-Knockout Mongolian Gerbils via CRISPR/Cas9 System - Wang, Yan; Zhao, Peikun; Song, Zidai; Du, Xiaoyan; Huo, Xueyun; Lu, Jing; Liu, Xin; Lv, Jianyi; Li, Changlong; Guo, Meng; Chen, Zhenwen (Frontiers in Bioengineering and Biotechnology, 2020)
The Mongolian gerbil (Meriones unguiculatus), a well-known "multifunctional" experimental animal, plays a crucial role in the research of hearing, cerebrovascular diseases and Helicobacter pylori infection. Although the whole-genome sequencing of Mongolian gerbils has been recently completed, lack of valid gene-editing systems for gerbils largely limited the further usage of Mongolian gerbils in biomedical research. Here, efficient targeted mutagenesis in Mongolian gerbils was successfully conducted by pronuclear injection with Cas9 protein and single-guide RNAs (sgRNAs) targeting Cystatin C (Cst3) or Apolipoprotein A-II (Apoa2). We found that 22 h after human chorionic gonadotropin (hCG) injection, zygote microinjection was conducted, and the injected zygotes were transferred into the pseudopregnant gerbils, which were induced by injecting equine chorionic gonadotropin (eCG) and hCG at a 70 h interval and being caged with ligated male gerbils. We successfully obtained Cst3 and Apoa2 gene knockout gerbils with the knockout efficiencies of 55% and 30.9%, respectively. No off-target effects were detected in all knockout gerbils and the mutations can be germline-transmitted. The absence of CST3 protein was observed in the tissues of homozygous Cst3 knockout (Cst3-KO) gerbils. Interestingly, we found that disruption of the Cst3 gene led to more severe brain damage and neurological deficits after unilateral carotid artery ligation, thereby indicating that the gene modifications happened at both genetic and functional levels. In conclusion, we successfully generated a CRISPR/Cas9 system based genome editing platform for Mongolian gerbils, which provided a foundation for obtaining other genetically modified gerbil models for biomedical research.